Financial Stress Among The Female University Students (Global Journal of Human-Social Science, 2026)
This study aimed to explore the financial stress of the female university student. Study also assesses the relationship between financial problems and financial stress. A questionnaire containing 32 positive and negative statements was administered to 100 female university students' of Bah din Zakiriya University. The psychometric properties were determined. The results show that it is a valid and reliable tool for measuring financial problems and its impact in the context of female university students .in order to test the research objects various statistical analysis were performed on the data and it was found that there is a significant positive correlation between financial problems and stress and financial stress. As far as the variation due to demographic are concerned students from the low income families are facing social rejection from teachers and peer groups.
Keywords: Causes of financial Problems; financial Stress; and female university students